2021
DOI: 10.1002/csr.2176
|View full text |Cite
|
Sign up to set email alerts
|

Media coverage, corporate social irresponsibility conduct, and financial analysts' performance

Abstract: We examine how financial analysts respond to public information about corporate social irresponsibility (CSI) conduct. Exploiting a novel dataset on environmental, social, and governance reputational risk rating based on media coverage and analyzing a sample of 667 public corporations over an 11-year period, we find that analysts' optimistic bias tends to grow in proportion to media coverage of CSI conduct. To deal with the endogeneity issue, we propose as instrumental variable, namely, the Euclidean distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Sustainability reports, as an important non-financial disclosure vehicle, have grown in importance for research and application in corporate strategic decisions, investment decisions, and resource allocation (Branco & Rodrigues, 2006;Dhaliwal et al, 2011). Previous research has found that corporate social responsibility (CSR) activities and accomplishments disclosed in sustainability reports improve a company's reputation (Berkan et al, 2021;Zhang et al, 2021) and increase the psychological value to investors when assessing a company's financial performance (Platonova et al, 2018), which can influence the company's market value (Gupta & Das, 2022;Liao et al, 2019). However, there is currently no standardized form of disclosure for sustainability reports, and their quality criteria are relatively vague, making assessing the quality of sustainability reports difficult (Koh et al, 2022;Rauf et al, 2020;Rauf et al, 2021;Usman, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability reports, as an important non-financial disclosure vehicle, have grown in importance for research and application in corporate strategic decisions, investment decisions, and resource allocation (Branco & Rodrigues, 2006;Dhaliwal et al, 2011). Previous research has found that corporate social responsibility (CSR) activities and accomplishments disclosed in sustainability reports improve a company's reputation (Berkan et al, 2021;Zhang et al, 2021) and increase the psychological value to investors when assessing a company's financial performance (Platonova et al, 2018), which can influence the company's market value (Gupta & Das, 2022;Liao et al, 2019). However, there is currently no standardized form of disclosure for sustainability reports, and their quality criteria are relatively vague, making assessing the quality of sustainability reports difficult (Koh et al, 2022;Rauf et al, 2020;Rauf et al, 2021;Usman, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Investors have also become subject to public pressure when corporations ignore environmental stakeholders. The resignation of Rio Tinto's CEO and senior executive team after the Australian Juukan Gorge debacle (Butler et al, 2020) was triggered by how financial investors responded to media report of irresponsible corporate conduct (Berkan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Using the Gulf Cooperation Council countries, Alazzani et al (2021) documented a positive relationship between analysts' recommendations and ESG disclosure and found that analysts assess ESG disclosure in firms with political connections as a strategic compliance. Berkan et al (2021) investigate the relationship between corporate social irresponsibility and financial analysts' performance and document that analysts tend to underestimate the effects of bad behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consistent with prior studies (Berkan et al, 2021;Duru & Reeb, 2002;Jackson, 2005), we use the error of analysts' forecasts (Error) and the optimistic bias of analysts' forecasts (Bias [Optimism]) as proxies for financial analysts' accuracy. Specifically, Error is the absolute value of the difference between the average of forecast earnings per share and the actual earnings per share divided by the stock price at the end of the last year (Berkan et al, 2021;Duru & Reeb, 2002). Bias (Optimism) is the value of the difference between the average of forecast earnings per share and the actual earnings per share divided by the stock price at the end of the last year (Huberts & Fuller, 1995;Jackson, 2005).…”
Section: Dependent Variablementioning
confidence: 99%